(untitled) (Scientific journal of the Fergana State University, 2025)
In contemporary English literature, spellonyms often appear in fantasy and magical realism genres. Examples include: "Wizard" a person with magical knowledge and powers. Example: "Gandalf" and "Dumbledore" from J.K. Rowling’s Harry Potter series. "Enchantment" is magic or spells performed by practitioners. Example: Magical objects in C.S. Lewis’s Narnia series. "Charm" is a magical object or phrase, often used for beneficial purposes. Example: Magical items in Neil Gaiman’s American Gods. Vladimir Propp’s the Morphology of the Folktale (1968) is a seminal work in folklore studies that primarily analyzes the structure and function of folktales. While Propp’s focus is on the narrative structure of folktales, his framework can be useful for understanding spellonyms and mythological elements in literature. Here’s how Propp’s work relates to spellonyms and myth. Propp’s functions often involve magical objects or actions. Spellonyms could be related to these elements, serving as names or terms that signify the power or purpose of magical items. Spellonyms might play a role in the transformation of characters or the resolution of conflicts, which are key functions in Propp’s model.In contemporary Uzbek literature, spellonyms—terms or names associated with magic or supernatural elements—are frequently used in both folk tales and modern fantasy works to evoke cultural heritage and create imaginative worlds. These terms often draw on traditional Uzbek folklore, mythology, and religious beliefs. Alpomish" is based on the legendary hero of Uzbek folklore, Alpomish is often depicted with magical prowess and heroic deeds. Modern works may reference Alpomish or similar legendary figures in fantasy contexts to highlight themes of bravery and magic. Spellonyms in English literature often reflect historical and cultural values. For example, beliefs about magic and witches from medieval and Renaissance Europe shape modern literature. English literature features spellonyms influenced by medieval folklore and literary traditions. For example, Shakespeare’s Macbeth includes magical elements like witches and prophecies.